2013
DOI: 10.5901/mjss.2013.v4n13p389
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Domestic Air Passenger Demand in the Republic of South Africa

Abstract: Analysing air passenger market is an integral part of air transport industry and form part of corporate planning process. This paper seeks to assess the determinants of domestic air passenger demand in the Republic of South Africa. The methodology used involved collection of data for passenger movements in South Africa for the period 1971 -2012 to determine the pattern of air travels. Data on macro and micro-economic variables considered to affect demand for air passenger travel were also collected. Multiple r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The study of Fernandes et al (2014), which analyzed Brazilian cities hierarchy as driver for airport development, also partially matches the findings of this paper, the difference being mainly to the reasons stated in the previous paragraphs, such as the elasticity of the demand to different drivers. All those independent variables considered by Torres et al (2015) and Baikgaki and Daw (2013), which were not considered in this study, present a future opportunity to enhance the model proposed here.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The study of Fernandes et al (2014), which analyzed Brazilian cities hierarchy as driver for airport development, also partially matches the findings of this paper, the difference being mainly to the reasons stated in the previous paragraphs, such as the elasticity of the demand to different drivers. All those independent variables considered by Torres et al (2015) and Baikgaki and Daw (2013), which were not considered in this study, present a future opportunity to enhance the model proposed here.…”
Section: Resultsmentioning
confidence: 95%
“…This conclusion matches the results found by Torres et al (2015), whose study found a high number of drivers of supply and demand for air transport services, meaning that the decision to provide (by airlines) and to use (by consumers) the service is affected by several factors. The study of Baikgaki and Daw (2013) also points for factors such as household income and the average price level of the air ticket, to significantly influence the regional aviation services. The study of Fernandes et al (2014), which analyzed Brazilian cities hierarchy as driver for airport development, also partially matches the findings of this paper, the difference being mainly to the reasons stated in the previous paragraphs, such as the elasticity of the demand to different drivers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional socioeconomic changes can expect a sharp decline in airport demand. The forecast error is positive, implying that the predicted value is greater than the actual value [ 11 ].…”
Section: Techniquesmentioning
confidence: 99%
“…The studies on factors affecting demand in air transport clearly show that GDP has a significant influence on air transport demand (Hutchinson, 1993;Alperovich & Machnes, 1994;Aderamo, 2010). Additionally, some studies found a high correlation between the variables of air transport and economic determinants (Ba-Fail, Abed & Jasimuddin, 2000;Baikgaki & Daw, 2013).…”
Section: Introductionmentioning
confidence: 99%